Diacylglycerol Kinase Alpha in Radiation-Induced Fibrosis: Potential as a Predictive Marker or Therapeutic Target - Liu, Chun-Shan; Schmezer, Peter; Popanda, Odilia (Frontiers in Oncology, 2020)
Radiotherapy is an efficient tool in cancer treatment, but it brings along the risk of side effects such as fibrosis in the irradiated healthy tissue thus limiting tumor control and impairing quality of life of cancer survivors. Knowledge on radiation-related fibrosis risk and therapeutic options is still limited and requires further research. Recent studies demonstrated that epigenetic regulation of diacylglycerol kinase alpha (DGKA) is associated with radiation-induced fibrosis. However, the specific mechanisms are still unknown. In this review, we scrutinized the role of DGKA in the radiation response and in further cellular functions to show the potential of DGKA as a predictive marker or a novel target in fibrosis treatment. DGKA was reported to participate in immune response, lipid signaling, exosome production and migration as well as cell proliferation, all processes which are suggested to be critical steps in fibrogenesis. Most of these functions are based on the conversion of diacylglycerol (DAG) to phosphatidic acid (PA) at plasma membranes, but DGKA might have also other, yet not well known functions in the nucleus. Current evidence summarized here underlines that DGKA activation may play a central role in fibrosis formation post irradiation and shows a potential of direct DGKA inhibitors or epigenetic modulators to attenuate pro-fibrotic reactions, thus providing novel therapeutic choices.